Liberalizing agricultural trade and developing countries - Orden, David; Kaukab, Rashid S.; Díaz-Bonilla, Eugenio (2003)
A diverse group of development and trade liberalization advocates agree that reduction of agricultural protection and subsidization in the world's wealthy countries is necessary to strengthen both international growth opportunities and the global trade regime. According to the consensus reached among participants attending a conference cosponsored by the Carnegie Endowment for International Peace and the Cordell Hull Institute, WTO Doha Round negotiations on agriculture should compel policy changes in industrialized countries to limit trade-distorting domestic subsidies for agricultural products, lower tariffs, increase market access, and eliminate export subsidies.In response to temporary hardships caused by an overall reduction in agricultural support, governments should have the flexibility to adopt temporary or limited domestic, and perhaps international, compensatory policies. Significant differences in perspective and policy prescriptions were expressed by conference participants about the appropriate speed and scope of agricultural liberalization in developing countries, especially if progress is not made toward reduced support for agriculture in developed countries.